Priority Actions and Progress to Substantially and Sustainably Reduce the Mortality, Morbidity and Socioeconomic Burden of Tropical Snakebite - Robert A. Harrison; José María Gutiérrez (Toxins, 2016)
The deliberations and conclusions of a Hinxton Retreat convened in September 2015, entitled “Mechanisms to reverse the public health neglect of snakebite victims” are reported. The participants recommended that the following priority actions be included in strategies to reduce the global impact of snake envenoming: (a) collection of accurate global snakebite incidence, mortality and morbidity data to underpin advocacy efforts and help design public health campaigns; (b) promotion of (i) public education prevention campaigns; (ii) transport systems to improve access to hospitals and (iii) establishment of regional antivenom-efficacy testing facilities to ensure antivenoms’ effectiveness and safety; (c) exploration of funding models for investment in the production of antivenoms to address deficiencies in some regions; (d) establishment of (i) programs for training in effective first aid, hospital management and post-treatment care of victims; (ii) a clinical network to generate treatment guidelines and (iii) a clinical trials system to improve the clinical management of snakebite; (e) development of (i) novel treatments of the systemic and local tissue-destructive effects of envenoming and (ii) affordable, simple, point-of-care snakebite diagnostic kits to improve the accuracy and rapidity of treatment; (f) devising and implementation of interventions to help the people and communities affected by physical and psychological sequelae of snakebite.